Proteomic analysis of Atg8-dependent recruitment of phagosomal proteins in the enteric protozoan parasite Entamoeba histolytica - Nakada-Tsukui, Kumiko; Watanabe, Natsuki; Shibata, Kumiko; Wahyuni, Ratna; Miyamoto, Eri; Nozaki, Tomoyoshi (Frontiers in Cellular and Infection Microbiology, 2022)
Autophagy is one of the bulk degradation systems and is conserved throughout eukaryotes. In the enteric protozoan parasite Entamoeba histolytica, the causative agent of human amebiasis, Atg8 is not exclusively involved in autophagy per se but also in other membrane traffic-related pathways such as phagosome biogenesis. We previously reported that repression of atg8 gene expression by antisense small RNA-mediated transcriptional gene silencing (gs) resulted in growth retardation, delayed endocytosis, and reduced acidification of endosomes and phagosomes. In this study, to better understand the role of Atg8 in phagocytosis and trogocytosis, we conducted a comparative proteomic analysis of phagosomes isolated from wild type and atg8-gs strains. We found that 127 and 107 proteins were detected >1.5-fold less or more abundantly, respectively, in phagosomes isolated from the atg8-gs strain, compared to the control strain. Among 127 proteins whose abundance was reduced in phagosomes from atg8-gs, a panel of proteins related to fatty acid metabolism, phagocytosis, and endoplasmic reticulum (ER) homeostasis was identified. Various lysosomal hydrolases and their receptors also tend to be excluded from phagosomes by atg8-gs, reinforcing the notion that Atg8 is involved in phagosomal acidification and digestion. On the contrary, among 107 proteins whose abundance increased in phagosomes from atg8-gs strain, ribosome-related proteins and metabolite interconversion enzymes are enriched. We further investigated the localization of several representative proteins, including adenylyl cyclase-associated protein and plasma membrane calcium pump, both of which were demonstrated to be recruited to phagosomes and trogosomes via an Atg8-dependent mechanism. Taken together, our study has provided the basis of the phagosome proteome to further elucidate molecular events in the Atg8-dependent regulatory network of phagosome/trogosome biogenesis in E. histolytica.